Serious Games Analytics
XXXIII, 477 p. 109 illus., 24 illus. in color.
Keywords: This first-of-its-kind reference moves the concepts and methodologies of game analytics and learning analytics into the emerging field of serious games. The book calls for more validated and standardized research into serious games analytics, backing up this demand with ways that player data can be transformed into information of value to the academic and serious games sectors. Featured methodologies derive from diverse disciplines, from computer science and data visualization to learning science and statistics. And the volume's second half highlights new frontiers for serious games in medical education and patient care, psychological profile generation, and learning support. Included in the coverage: A meta-analysis of data collection in serious games research. Measuring expert-performance for serious games analytics: from data to insights. Comparative visualization of player behavior for serious games analytics. The role of serious games in robot exoskeleton assisted rehabilitation of stroke patients. Design of game-based stealth assessment and learning support. A game design methodology for generating a psychological profile of players. Serious Games Analytics gives educators, instructional designers, and researchers in educational technology a fuller grasp of the knowledge learners access in serious game play, and data and ideas leading to the next wave of serious games. .